52 Prognostic implication of contrast induced acute kidney injury – a five year mortality review. (16th October 2019) - Jones, J; Menown, I; Kurth, M; McEneaney, D; Kinnin, M; Harbinson, M; Morgan, N
Abstract : Background/Introduction: Contrast induced acute kidney injury (CI-AKI), defined as a delta rise in creatinine of >26.5 µmol/L or a 50% relative rise within 48 hours following iodinated contrast, is associated with considerable mortality risk. Our previous study of 301 consecutive Chronic Kidney Disease (CKD) patients undergoing contrast coronary angiography/percutaneous coronary intervention (PCI) highlighted a CI-AKI rate of 9.3% at index procedure. Few studies have looked at long term prognosis, adverse events and mortality following CI-AKI. Objective: Our objective was to assess the 5 year mortality rate following contrast coronary angiography and to evaluate independent risk factors and presence of index CI-AKI on 5 year mortality. Methods: A prospective cohort study in a single cardiology centre in the UK was carried out from 2011–2013, the results of which have been previously published. In total 2, 519 patients were screened, 321 (12.7%) of which had CKD, which was defined as a Glomerular Filtration Rate (GFR) of <60 mls/min/m 2 . In total a final cohort of 301 (93.7%) CKD patients were recruited. Written consent was obtained from all patients. Patient demographics, CI-AKI risk factors, CKD stage and contrast dose at initial contrast angiography were recorded. A Mehran risk score was calculated for each patient. Samples for plasma NGAL, serum L-FABP, serum KIM-1, serum IL-18 and serum creatinine were previously collected pre and post contrast angiography and statistically analysed to assess prediction of CI-AKI as previously described. At 5 years, following index contrast procedure, we analysed for MACE and mortality by accessing electronic medical records. Patient consent was granted to access medical notes. Baseline risk factors, Mehran risk score and index biomarker results were analysed to determine predictability of 5 year mortality. Statistical analysis was performed to assess the predicative ability of CI-AKI risk factors and Mehran risk score on 5 year mortality risk. Results: At 5 years follow up data was available for 292 (97%) of the original 301 patients. Type 2 diabetes, contrast volume, Mehran risk score, lower glomerular filtration rate (GFR) and use of intravenous fluids at index procedure were independently associated with five year mortality, p<0.05. A Mehran score ≥10 had an AUC of 0.67, p<0.001, sensitivity 65%, specificity 67%, PPV 41%, NPV 85%, RR 2.7 and OR 3.9 for five year mortality. At 5 year follow up 76 (26.0%) of the total patient cohort had died. Out of the 28 patients who developed CI-AKI at index contrast procedure 17 (60.7%) of the 28 patients had died at 5 years versus 58 (22.0%) of the 264 non CI-AKI patients (p<0.001). At 5 year follow up MACE occurred in 20 (71.4%) of the 28 CI-AKI patients versus 78 (29.5%) of the 264 non CI-AKI patients (figure 1 ). Conclusions: This study highlights that index CI-AKI is an independent risk factor for 5 year mortality and MACE. Several risk factors act independently as surrogate markers of CI-AKI prior to administration of iodinated contrast, many of which are incorporated in the Mehran CI-AKI risk score. Furthermore, these are associated with adverse incidents and mortality at five years following index contrast procedure. A combination approach of these findings, including novel biomarkers as previously demonstrated, will help to reduce risk and identify early CI-AKI to facilitate timely therapeutic intervention. Table 1 highlights the 5 year mortality and MACE data in patients with and without baseline CI-AKI, showing a significantly higher proportion of patients with baseline CI-AKI developing mortality or MACE following index contrast. Table 2 illustrates predictability of index biomarker results for 5 year mortality, showing a statistically significant prediction across all biomarkers.